Configurações subjetivas da participação política de militantes do movimento estudantil na Universidade Federal do Espírito Santo - Meira, Everton Faria (2020)
The subjectivity of militants of the student movement - SM - can stimulate their political participation and the reproduction of vices of the Brazilian party political logic - distinction between representatives and those represented, excessive autonomy o